(untitled) (Al-Academy, 2026)
The world is witnessing today a clear and tangible overlap in everything that accompanies human life on the technical and cognitive level in order to serve humanity and provide all the requirements that help in creating an integrated and ideal environment has also been reflected in other side activities represented by the entertainment aspect, a large part of which is sports. Contemporary artistic methods that depend on the scenographic system have led to the overlap of the fields of contemporary plastic art with other activities. Sports constitute one of the activities that receive special attention due to the interest of the largest segment of the world’s population in practicing or following it, which has made many countries seek to host a sports championship at the global or continental level. This makes the host country more interested in preparing and organizing an artistic festival that depends on multiple contemporary techniques according to a scenographic system in which several styles and techniques of contemporary art in all its sections are combined in order to arouse amazement or shock during its presentation and to mobilize the largest possible number of followers inside the stadium or via satellite broadcast networks in a manner consistent with the nature and culture of the host country in order to familiarize other countries more with its civilization and heritage, and to produce an artistic show that affects the recipient’s soul and carries Intellectual dimensions linked to several messages and speeches addressed to the entire world.